Enhancement of the rancidity stability in a marine‐oil model by addition of a saponin‐free quinoa (Chenopodium quinoa Willd.) ethanol extract. Issue 9 (5th April 2017) - Miranda, Margarita; Barbosa, Roberta G.; Trigo, Marcos; Uribe, Elsa; Vega‐Gálvez, Antonio; Aubourg, Santiago P.
Abstract : This research focused on the antioxidant capacity of quinoa ( Chenopodium quinoa Willd.), being its basic objective to analyze the retention of this property in the case that a previous saponins removal by water washing was undertaken. Chemical analyses related to saponin content and antioxidant behavior were carried out on ethanolic extracts of two quinoa ecotypes (Ancovinto and Cancosa) and compared to quinoa that was not subjected to saponins extraction; comparison to positive control (BHT‐including condition) was also achieved. Lower contents on total polyphenols, total flavonoids and γ‐tocopherol, and antioxidant activity (DPPH assay) were observed in saponin‐free quinoa extracts from both ecotypes when compared with their saponin‐including counterpart. Further, the effect of the different kinds of quinoa extracts was comparatively analyzed in a marine‐oil heated model system. As a result, saponin‐free quinoa extracts led to marked lipid oxidation inhibition assessed by the determination of conjugated dienes, peroxides, thiobarbituric acid reactive substances, and polyenes, this effect being similar to the one produced by saponin‐including quinoa extracts. Consequently, the water‐washing process did not produce a detrimental effect over the inhibitory capacity of lipid oxidation of quinoa grain when evaluated in a lipid‐food system with high degree of unsaturation (i.e., marine‐oil model). Practical application: Quinoa ( Chenopodium quinoa Willd.) is a highly appreciated pseudo‐cereal of Andean origin that has shown a wide range of profitable nutritional and functional properties. However, saponin compounds located in the pericarp of quinoa seed are bitter and interfere with its palatability and digestibility, making difficult to use this grain as a practical food source for commercial processing. In the present study, the antioxidant behavior of a saponin‐free quinoa was investigated and compared to its counterpart saponin‐including quinoa. As a result, although the elimination of saponins of quinoa grain led to a loss of phenolic compounds and a consequent decrease in antioxidant activity (assessed by the method of DPPH), this process did not produce a detrimental effect over the inhibitory capacity of lipid oxidation when evaluated in a marine‐oil model. Such pre‐treatment would avoid the inconveniences of saponins presence while providing a source of potential food additives including antioxidant properties. Total saponin content and antioxidant properties and effectiveness of saponin‐free quinoa (content on total polyphenols, flavonoids and tocopherols, DPPH assay, and antioxidant capacity in a heated marine‐oil model system) are comparatively studied with quinoa including saponin compounds, taking into account two different quinoa ecotypes (i.e., Ancovinto and Cancosa). As a result, saponin‐free quinoa provides a suitable product including lipophilic‐type antioxidant molecules, susceptible to develop an active preservative role in lipid‐food systems with high degree of unsaturation. Abstract : Total saponin content and antioxidant properties and effectiveness of saponin‐free quinoa (content on total polyphenols, flavonoids and tocopherols, DPPH assay, and antioxidant capacity in a heated marine‐oil model system) are comparatively studied with quinoa including saponin compounds, taking into account two different quinoa ecotypes (i.e., Ancovinto and Cancosa). As a result, saponin‐free quinoa provides a suitable product including lipophilic‐type antioxidant molecules, susceptible to develop an active preservative role in lipid‐food systems with high degree of unsaturation.